2011
DOI: 10.3390/ijerph8010097
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Handwashing with Water or Soap on Bacterial Contamination of Hands

Abstract: Abstract:Handwashing is thought to be effective for the prevention of transmission of diarrhoea pathogens. However it is not conclusive that handwashing with soap is more effective at reducing contamination with bacteria associated with diarrhoea than using water only. In this study 20 volunteers contaminated their hands deliberately by touching door handles and railings in public spaces. They were then allocated at random to (1) handwashing with water, (2) handwashing with non-antibacterial soap and (3) no ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
160
1
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(189 citation statements)
references
References 14 publications
7
160
1
21
Order By: Relevance
“…These may lead to acquisition of resistance genes by the organism. Burton et al (2011) in London, UK, reported that hand washing with plain non-bacterial soap resulted in a significant reduction in bacterial hand carriage. In this study, the antibacterial soaps gave more significant results as some of the isolates were completely eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may lead to acquisition of resistance genes by the organism. Burton et al (2011) in London, UK, reported that hand washing with plain non-bacterial soap resulted in a significant reduction in bacterial hand carriage. In this study, the antibacterial soaps gave more significant results as some of the isolates were completely eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated hands serve as vehicles of transmission of infectious diseases (Ogba et al, 2016) which may increase infection rates among children. Hand washing is the most effective and simple method of preventing the spread of communicable diseases (Burton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent laboratorybased study in the United Kingdom similarly found that the presence of fecal bacteria was reduced by 23% by handwashing using water alone. 23 A community-based observational study in Bangladesh reported that children who lived in households where food preparers briefly washed their hands with water alone experienced significantly less diarrhea than children living in households where food preparers did not wash their hands at all. 4 Other evaluations suggest that washing hands with water alone can reduce the amount of bacteria 8,28,35,36 but not to the same extent as bar soap.…”
Section: Discussionmentioning
confidence: 99%
“…22 A 15 second scrubbing time was close to the observed average hand scrubbing time of 12.5 seconds found in a study in urban Kamalapur, Dhaka 6 and the observed average hand scrubbing time of 14 seconds found in the United Kingdom. 23 Thirty seconds of scrubbing was the maximum scrubbing time observed after receiving the soap intervention in the Kamalapur study. 6 The fieldworker visited each mother five times to collect a total of 10 hand rinse samples from each mother (Figure 1).…”
Section: Methodsmentioning
confidence: 97%
“…The duration ranged on average as short as 20 seconds to 30 seconds, including rub the backs of hands, wrists, between fingers and under fingernails [1,7]. Hand washing with soap and water is more effective for the removal of bacteria than washing with water alone to 23% [8].…”
Section: Introductionmentioning
confidence: 99%